The Existence of Islamic Law in Indonesia in the Millennial Era in Supporting the Sustainable Development Goals (SDGs): Maqashid Sharia Perspective - Muthoifin; Nuha; Ishmah Afiyah (Walidem Institute and Publishing (WIP), 2025)
Objective: This study aims to analyze the existence of Islamic law in Indonesia in the millennial era in supporting the achievement of the Sustainable Development Goals (SDGs) through the perspective of Maqashid Sharia. Theoretical framework: The theoretical framework used is the theory of Maqashid Syariah Al-Ghazali and Al-Shatibi which emphasizes the five main aspects of protection: religion, soul, intellect, heredity, and property. Literature Review: This review is based on a literature review that includes the development of Islamic law in Indonesia, its relevance to the goals of the SDGs, and the relevance of Maqashid Syariah as a conceptual framework to bridge between sharia principles and modern needs. Methods: The research method used is qualitative with a literature study approach. Data was obtained through the analysis of documents, such as Islamic law regulations in Indonesia, public policies related to the SDGs, and the latest scientific articles. The analysis was carried out in a descriptive-analytical manner to evaluate the contribution of Islamic law to social, economic, and environmental sustainability. Results: This study shows that Islamic law in Indonesia, such as zakat, waqf, and sharia financing, has contributed significantly to poverty alleviation (SDG 1), improvement of quality education (SDG 4), and reduction of inequality (SDG 10). The Maqashid Sharia approach allows Islamic law to continue to be relevant in facing the challenges of the millennial era, especially through adaptation to digital technology and inclusion-based economic development. Implications: This study shows that the strengthening of Islamic law based on Maqashid Sharia can be a unique and contextual model of sustainability for Indonesia. This result also encourages legislation and public policy to further integrate Islamic values in efforts to achieve the SDGs. Novelty: The novelty of this research lies in the merger of Islamic law, Maqashid Sharia, and SDGs in the context of the millennial era. This study offers a new perspective on how Islamic law is not only relevant but also instrumental in supporting the global development agenda while maintaining sharia principles. This integration provides a strategic framework for the development of Islamic law in Indonesia in supporting holistic and inclusive sustainability.